Perancangan Sistem Informasi Meeting Report PT. Angkasa Pura II Kc. Sulthan Thaha Jambi - Efitra, Efitra; Ridho, M.Fawwaz; Andika, Andika; Kholaf, Badarudin; Liyani, Febby; Handayani, Sri (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2023)
Aplikasi